Analisis Keuntungan Dan Kelayakan Industri Pengolahan Tahu Pong “Mayang” Di Kelurahan Loktabat Selatan Kecamatan Banjarbaru Selatan - Mutmainna; Mahdalena, Zulipah; Rohansyah (Fakultas Pertanian UVAYA Banjarmasin, 2023)
This study aimed to determine the cost of production , revenue,profits, and the feasibility of the Tofu Pong “Mayang” processing Industry in the South Loktabat village, shouth Banjarbaru district. The Sampling method used is the Case Study method. . While the Data Collection technique is through direct observation and interviews. The results of this study obtained that the total cost (production cost) was Rp.29.211.055,-/month, the amaunt of Revenue was Rp. 63.999.000,-/month, the Profit earned was Rp.34.369.000,-/month, and the feasibility (RCR) was 2,19. From the RCR valur, it can be said that the Tofu Pong “Mayang” proseccing industry in the South Loktabat Village is feasible to cultivated